2015
DOI: 10.1016/j.jspd.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Can Intraoperative Spinal Cord Monitoring Reliably Help Prevent Paraplegia During Posterior Vertebral Column Resection Surgery?

Abstract: The prevalence of SCM changes during PVCR above the conus medullaris was 16.7%, mostly during osteotomy and rod/screw compression. Data returned with prompt intervention and all had intact lower extremity motor function postoperatively. These SCM "saves" strongly emphasize the importance of multimodality neurophysiologic monitoring during high-risk cases, minimizing postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Injury to the spinal cord or the nerve roots is one of the most important complications of PVCR. (7,14). We have used neural intra-operative monitoring routinely and observed no exacerbation of the preoperatively existing neurologic status.…”
Section: █ Resultsmentioning
confidence: 99%
“…Injury to the spinal cord or the nerve roots is one of the most important complications of PVCR. (7,14). We have used neural intra-operative monitoring routinely and observed no exacerbation of the preoperatively existing neurologic status.…”
Section: █ Resultsmentioning
confidence: 99%
“…However, with various intraoperative responses including raising the MAP, removing any traction on the patient, or reversing previously applied correction maneuvers, all patients had return of data to acceptable limits without any major neurologic deficits sustained. 28 Jarvis et al demonstrates the effectiveness of MEP changes in guiding surgical intervention. The authors identified highrisk steps of the procedure and methods to successfully improve monitoring changes.…”
Section: Neurologic Complications In 3-column Osteotomiesmentioning
confidence: 99%
“…However, with various intraoperative responses including raising the MAP, removing any traction on the patient, or reversing previously applied correction maneuvers, all patients had return of data to acceptable limits without any major neurologic deficits sustained. 28…”
Section: Neurologic Complications In 3-column Osteotomiesmentioning
confidence: 99%